Academic Safety Planning: Intervening to Improve the Educational Outcomes of Collegiate Survivors of Interpersonal Violence - Voth Schrag, Rachel J. (Journal of interpersonal violence, 2022)
Demonstrated impacts of intimate partner violence (IPV) and sexual assault (SA) for college students include negative outcomes related to mental, physical, emotional, and academic well-being. As a result of increasing awareness of the long-standing epidemic of IPV and SA on college campuses, Institutions of Higher Education (IHEs) are expanding the services provided to survivors of IPV and SA, including campus-based advocacy services that are adapted from community models. Like community advocacy, campus-based advocacy services focus on empowerment, support, resource provision, and addressing safety needs. However, the unique context of higher education produces specific student-centered needs, including an increased focus on educational goals, academic accommodations, and safety planning. The current study seeks to shed new light on the specific foci and tasks of advocacy in the context of IHEs, related to what we call ?academic safety planning,? and to highlight the experience of student service recipients utilizing these forms of advocacy. Thematic analysis of 48 qualitative interviews with advocates (n = 23) and service users (n = 25) from five programs at three universities was used to discover practices applied by campus-based advocates and to understand student-survivor needs and preferences within academic safety planning. Findings reveal the core components of academic safety planning, which are: (a) Advocating for emotional and physical safety in the university context, (b) Assessing and identifying needed academic accommodations, and (c) rebuilding connections and institutional trust at school. These interviews reveal that academic safety planning has the potential to enhance the academic outcomes of survivors, which in turn could lead to important improvements in long-term personal safety, well-being, and economic security for student-survivors.